Kewenangan Judicial Review oleh Mahkamah Konstitusi dan Implikasinya terhadap Sistem Hukum di Indonesia - Winanta, Rendro Prastyan; Anna Erliyana (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The Constitutional Court (MK) has important implications for the legal system in Indonesia. The Judicial Review carried out by the Constitutional Court acts as a key mechanism in maintaining the constitutionality of laws, including Government Regulations in Lieu of Laws (PERPPU) and regional regulations. The Constitutional Court has the authority to examine laws against the 1945 Constitution, functioning as a controller and balancer in the exercise of state power. In this research, data will be collected through a literature study which includes legal literature, journal articles and official documents from the Constitutional Court. This research will also involve qualitative analysis of Constitutional Court decisions related to Judicial Review, including their impact on public policy and the protection of constitutional rights. In addition, interviews with legal practitioners, academics and members of the Constitutional Court can be conducted to gain a broader perspective regarding the challenges and successes in implementing the Judicial Review authority. The analytical method used in this research is descriptive and comparative analysis. Descriptive analysis will be used to describe the Constitutional Court's authority in the context of Judicial Review, while comparative analysis will compare the practice of Judicial Review in Indonesia with other countries that have similar legal systems. Research shows that the Constitutional Court's decision, as in several decisions, has a significant impact on the investigation process and the protection of citizens' constitutional rights. The Constitutional Court's authority in resolving election disputes has also received attention, where the Constitutional Court plays a vital role in ensuring justice and transparency in the democratic process. Apart from that, the Constitutional Court is faced with challenges in exercising its authority, including conflicts with other institutions and the need to reorient the Judicial Review authority. The implications of this Judicial Review authority are very broad, including legal and governmental stability. The Constitutional Court's decision not only affects existing regulations, but can also form new legal norms that have the potential to strengthen or weaken the existing legal system. Therefore, it is important to have a deep understanding of the Constitutional Court's authority and its impact on the legal system, as well as the need to strengthen regulations that support the implementation of Judicial Review effectively and efficiently.